Design and Finite Element Analysis of Hybrid Carbon/Glass Fiber-Reinforced Epoxy Composite Automotive Drive Shaft - M. Soliman, Mohamed A. Badie (2007)
Weight reduction, fatigue resistance, vibration damping and design flexibility to meet critical vibration characteristics are offered by substituting fibrous composites for conventional metals in power transmission shafts, which utilized in many applications including automotive. Strongly related to stiffness, the optimal design constrained by rotational frequency, torsional frequency and applied torque, which are to be traversed by increasing the critical speed, torsional stiffness and critical torque, respectively. However, composite drive shaft (DS) design is a problem of prescribed stiffness with the variables of layers material, thickness and stacking. Least cost can be achieved by using a hybrid of carbon/epoxy and E-glass/epoxy as carbon fibers with their higher specific stiffness, have comparatively high price. The main objectives are to study the effect of fiber orientation angles and stacking sequence on the natural frequency, buckling strength and fatigue life. Besides, the study of the torsional stiffness and failure modes of composite tubes, are included in the objectives.